Business Strategy for PT. Bhakti Usaha Era Makmur in Purpose to Increase Sales - Yosheko, Tita Gracia; Aldianto, Leo (The Indonesian Journal of Business Administration, 2014)
Abstract - Albizia is a plan with high functional value and also reasonable price. As a trading company, PT. Bhakti Usaha Era Makmur is trading albizia timber. Currently, there are several disadvantages situation for West Java business segment. Decreasing number of suppliers, high uncollectible receivable, and low customer demand satisfaction are became company business issues for recent years. Those three business issues will be analyzed by Carter 10 Câ€™s, value chain etc. The root causes are legal agreement cannot implemented properly, few customers were active, and delegated primary activity to suppliers.. Considering the root cause and objective, and also remembering the business life cycle of company which is in growth stage, the author propose that company is conducting backward vertical integration. The strategy is completed with financial analysis, which is resulting positively (IRR 64% and BEP in 4 years).Â Keywords: Agribusiness, Ablizia, Vertical Integration, Business Strategy